Hubungan Pengetahuan, Persepsi, Sikap, dan Sarana-Prasarana dengan Perilaku Personal Hygiene Saat Menstruasi pada Santriwati di Pondok Pesantren Tahfidzil Qur'an Daarussa'adah Pesawaran Tahun 2026 - Anggie Pebriani; Dhiny Easter Yanti; Christin Angelina Febriani (Jurnal Sains dan Kesehatan, 2026)
Personal hygiene practices during menstruation is important to maintaining the reproductive health of adolescent girls and preventing reproductive organ infections. Poor hygiene causes post-menstrual problems in 5.2 million adolescents in Indonesia, such as reproductive tract infections, urinary tract infections, pathological vaginal discharge, fungal infections, genital area irritation, and unpleasant odor. Factors influencing personal hygiene practices during menstruation include knowledge, perceptions, attitudes, and infrastructure. This study was aimed determine the relationship between knowledge, perceptions, attitudes, and infrastructure and personal hygiene practices during menstruation among female students at the Daarussa'adah Qur'an Tahfidzil Islamic Boarding School in Pesawaran in 2026. This study was quantitative with a cross-sectional approach. The population was all female students at the Daarussa'adah Qur'an Tahfidzil Islamic Boarding School in Pesawaran, and a sample of 74 respondents was selected using total sampling. Data analysis used the chi-square test with a significance level of 95%. The results of the study showed a relationship between knowledge (p-value = <0.001; OR = 279.000), perception (p-value = <0.001; OR = 620.000), attitude (p-value = <0.001; OR = 165.333), and infrastructure (p-value = <0.001; OR = 0.002) and personal hygiene behavior during menstruation. Suggested for the Islamic boarding schools include routinely improving reproductive health education regarding personal hygiene during menstruation and providing adequate infrastructure to support the development of good knowledge, perceptions, and attitudes, so that female students can optimally implement personal hygiene behaviors during menstruation.